Pengajaran Dan Pembelajaran Bahasa Arab Di Sekolah-Sekolah Menengah Di Semenanjung Malaysia - Permasalahan Dan Cara Mengatasinya - Ismail Abdullah; Mohd Alwi Yusoff; Muhamad Muda (Universiti Sains Islam Malaysia, 2024)
The main purpose of this research was to study the teaching and learning of Arabic Language in secondary schools in Peninsular Malaysia -problems &problem solving. The teaching of Arabic Language was compared with the teaching of other languages - espeacially Bahasa Malaysia and English Language, on various issues such as the level of importance, the level of interest and the degree of dzfficulties. The perception of the students towards the Arabic language, the pedagogy and the techniques of teaching the language, the textbook, the reference book & the activity book were also examined. The research utilized a studpcase approach using quistionnaire. The sample consisted of l000 student respondents from 40 Islamic Relegious Schools in Peninsular Malaysia. The study found that - in general - the students considered Arabic Language is among the most important languages Besides English and Bahasa Malaysia and considered one of the most dzfficult subjects if the textbooks, the classroom activities, the syllabus and the learning invironment are not well organized and prepared. However the student respondents are very keen to learn Arabic Language without any hassle. Finally the research proposed certain policies and techniques recommendations towards the teaching and learning of Arabic which could help the students, the teachers and theschools in solving the problems that arose during the teaching and learningprosess in the classroom.